Advanced Practice Nursing: “Training” Pillar in Supporting the Proposal in Brazil - Cristina Maria Garcia de Lima Parada; Elisabete Pimenta Araujo Paz; Lucia Yasuko Izumi Nichiata; Dulce Aparecida Barbosa; Luciane Kantorski (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to present the pillars that support what has been called Advanced Practice Nursing and discuss the necessary training for its implementation. Methods: elements contained in assessment documents for graduate programs proposals, reports of presentations by international professors in countries and selected scientific publications were gathered to compose the argument. Results: practice/competency (adds broad and in-depth knowledge about health processes and scientific evidence, clinical reasoning and clinical skills for therapeutic indications); 3) professional regulation (corresponding legislation and monitoring); and 4) funding (broad training and professional practice policy). Final Considerations: the agenda for implementing Advanced Practice Nursing in Brazil involves joining efforts to identify stakeholders for a work to legitimize their importance in the country’s health and education overview.